Caso de estudio: Promart Homecenter - Carpio Hinojosa, Angeli (2022)
In this work, Promart Homecenter will be taken as the research company. Promart belongs to the Home Center sector, its industry being modern retail stores (retail format). This research aims to analyze the company both in its external and internal environment, that is, opportunities and threats, as well as strengths and weaknesses, with this information, it will be possible to diagnose the situation in which the company finds itself with respect to its industry and its position with its competitors. To situate the reader, in this work the Strategic Management methodology is being used, using tools and matrices such as SWOT, Peyea, MCPE, Value Chain, PEST, Porter's 5 forces, among others. All these will be treated and deepened throughout the research work, the result of the combination of these tools and the analysis of the information collected, will allow managers to make decisions regarding the course and future of the company, it will also provide a range of strategies to put into action, and deal with both external and internal factors that are currently affecting the Company In addition to the above, a factor will become very important in the development of work and will be a determining factor in decision making, Sustainability is a quality in companies that consumers and customers are gradually appreciating, this will play an essential role for the implementation of strategies.